Leaving Parnassus : the lyric subject in Verlaine and Rimbaud - Whidden, Seth, 1969- (Faux titre, 2007)
Leaving Parnassus: The Lyric Subject in Verlaine and Rimbaud considers how the crisis of the lyric subject in the middle of the nineteenth century in France is a direct response to the aesthetic principles of Parnassian poetry, which dominated the second half of the century much more than critics often think. The poets considered here rebel against the strict confines of traditional and contemporary poetry and attempt to create radically new discursive practices. Specifically, the close readings of poems apply recent studies of subjectivity in poetry and focus on the works of Paul Verlaine and.